2008
DOI: 10.1364/oe.16.015238
|View full text |Cite
|
Sign up to set email alerts
|

Thin film solar cell design based on photonic crystal and diffractive grating structures

Abstract: In this paper we present novel light trapping designs applied to multiple junction thin film solar cells. The new designs incorporate one dimensional photonic crystals as band pass filters that reflect short light wavelengths (400 - 867 nm) and transmit longer wavelengths(867 -1800 nm) at the interface between two adjacent cells. In addition, nano structured diffractive gratings that cut into the photonic crystal layers are incorporated to redirect incoming waves and hence increase the optical path length of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(110 citation statements)
references
References 14 publications
1
107
0
1
Order By: Relevance
“…36,37 Other approaches with Bragg reflectors have also been proposed to avoid parasitic absorption. 12,13 We find that a separation of the grating and rear reflector is necessary, not only for Al, but also for a less absorbing Ag reflector.…”
Section: B Implementation In Solar Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…36,37 Other approaches with Bragg reflectors have also been proposed to avoid parasitic absorption. 12,13 We find that a separation of the grating and rear reflector is necessary, not only for Al, but also for a less absorbing Ag reflector.…”
Section: B Implementation In Solar Cellsmentioning
confidence: 90%
“…Such structures have been thoroughly analyzed in the past, [8][9][10] but have attracted renewed attention lately. [11][12][13][14] Recently, it has been shown that periodic structures may increase light trapping beyond that of the Lambertian 4n 2 limit, 15,16 but with a significant angular dependency. At the same time, it has also been shown that bi-periodic gratings, in general, are expected to a)…”
Section: Introductionmentioning
confidence: 99%
“…A quantity for band edge enhancement, the enhancement factor (Ef ), is defined as the ratio of the average absorption of a modified concentrator system with a PhC-based slab to the average absorption of a concentrator system with a solid slab of equivalent volume. For a given spectrum range near the band edge (1100 nm), the evaluation of the enhancement factor is calculated using the formula [23] …”
Section: Comparison Of Various Nano-structured Solar Cell Concentratorsmentioning
confidence: 99%
“…박막형 구조의 경우 흡수 층이 얇아 입사한 광자가 이동하는 경로가 짧아지기 때문에 일반적인 구조에 비해 상 대적으로 흡수효율이 떨어지게 된다. 그래서 실리콘 흡수 층 아래에 유전체 기판이나 금속 반사경을 배치하는 등의 구조 적 변화를 통해 광자의 이동경로를 증가시켜 흡수 효율을 높 이고자 하는 노력이 계속되고 있다 [2,3,4] . 의 모드간에 적절한 위상 정합 조건이 만족되면 서로 간에 강한 결합이 생기게 되고, 입사된 빛은 유전체 내부에서 유 전체를 따라 진행하게 되는데 이를 도파모드 공진이라 한다 [5,6,7] .…”
Section: 서 론unclassified